Analysis of the Quality of Registration Counter Services Based on the SERVQUAL Model (Case Study at Kaimana Hospital) - Hasnah Tapa; Ika Devi Pramudiana; Dian Feriswara; Feri Ramadhan (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Registration counter services as the main gateway for patient interaction with hospitals play a crucial role in shaping public perception of the quality of health services. However, Kaimana Hospital faces challenges such as long queues, limited physical facilities, and reliance on coordination between units, which have the potential to reduce patient satisfaction. This study aims to analyze the gap between patients' expectations and perceptions of the quality of registration counter services using the SERVQUAL model, focusing on five dimensions: Reliability, Assurance, Tangibles, Empathy, and Responsiveness (responsiveness). The qualitative-descriptive method is applied through direct observation during the workday, semi-structured interviews and analysis of secondary documents. The results of the study showed that officers were considered competent in providing Assurance information and showed spontaneous empathy for the Empathy vulnerable group. However, the Reliability dimension is hampered by long queues and reliance on the availability of medical personnel, while Tangibles is limited to physical facilities that are less adaptive during visitor density. Responsiveness is also influenced by fluctuations in the number of patients and coordination between units that are not optimal. The main gap lies in the absence of a digital queuing system, structured inclusive protocols, and standardization of officer competencies. Strategic recommendations include certification-based HR training, integration of digital queue technology, infrastructure optimization, and strengthening operational coordination. This research emphasizes the importance of a holistic approach to create an inclusive, efficient, and sustainable service ecosystem, as well as a reference for regional hospitals in improving the quality of services based on the SERVQUAL model.